A summary and synthesis of procedural regulations and standards—Informing a procedures writer's guide. (November 2016) - Peres, S. Camille; Quddus, Noor; Kannan, Pranav; Ahmed, Lubna; Ritchey, Paul; Johnson, William; Rahmani, Samina; Mannan, M. Sam
Abstract: Well-written procedures are an integral part of any industrial organization for safe operation, managing risks, and continuous improvement. Regulatory bodies around the world require industries to have current, accurate, and appropriate procedures for most processes. Although the importance of procedures is recognized by all industries in general, significant incidents still occur due to procedural breakdowns. Some of the procedural breakdowns come from obvious problems such as the procedure not being available or the procedure being wrong. However, some incidents have occurred when correct procedures were available and the operator used those procedures. In these instances, the reason workers do not follow procedures correctly may be attributable the procedure being presented or designed in a manner that does not sufficiently communicate the information in a manner that is easily and quickly understood. This indicates that procedure writers may need more guidance on how to write and design procedures so they accomplish this. To effectively manage risk, procedures need to be technically correct (and regulatory compliant) and usable. As part of this, the current work is focused on developing a systematic approach to a procedure writer's guide that includes a regulatory compliant component. The work presented here consists of an effort to identify procedure-writing practices necessary to ensure regulatory compliance by summarizing a large sample of regulations and standards from several industries. The regulations and standards were organized to reflect common ideas and the implications in terms of human factors needs for procedure design were identified. This information will be used as part of the development of a writer's guide that accounts for human factors (HF) that includes explanations of HF implications and empirical support for each of the guidelines. The novelty of the method and information presented here is in the idea of leveraging the cumulative information available regarding procedures in regulations and standards. Incorporating this information into a procedure's writers guide in this manner may not only facilitate procedure being regulatory compliant for facilities in different geographies of the world, but could also support their being written with considerations for human performance. Highlights: This paper presents an analysis of regulations and standards related to procedures from 10 entities across the world. Analyses grouped 80 discrete regulations and standards related to procedures into 29 elements (themes) and 5 categories. The analyses facilitated the development of a writer's guide that supports regulatory compliance.